Pengembangan Program Stretching Berbasis Kebutuhan Atlet Renang: Studi Kualitatif di Universitas Negeri Medan - Gilang Pratama; Andra Z Ginting; Yesekiel Nababan; Gilbert Maringga; Nurhayati Simatupang (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Stretching is a critical yet often overlooked component in the training programs of competitive swimmers. This study aimed to develop a structured, needs-based stretching program for swimming athletes at Universitas Negeri Medan. A qualitative approach was employed, using semi-structured interviews with 16 participants (12 active swimmers and 4 coaches), passive participatory observation across 8 training sessions, and a 4-week pilot trial to evaluate the program's effectiveness. Data were analyzed thematically following Braun and Clarke's (2006) six-phase framework. Findings revealed that none of the athletes followed a formally structured stretching program, and coaches lacked evidence-based guidelines. A three-phase program was developed comprising dynamic stretching (10–15 minutes pre-training), sport-specific stretching (2–5 minutes per recovery segment during training), and static stretching (15–20 minutes post-training). The pilot trial demonstrated a mean improvement of 19.0° in shoulder range of motion and a reduction of 1.6 seconds in 50-meter swim time after four weeks of implementation. Validated by all four coaches, the program is applicable, evidence-based, and adaptable to the resource constraints of Indonesian university swimming programs.